Integration of Geographic Information System (GIS) and Analytical Hierarchical Process (AHP) for Dams site selection in Wadi Numan watershed in the Holy City of Mecca - Hakeem, Oula Ali; Ouerghi, Sarra Al-Habib (Arab Journal for Sciences and Research Publishing, 2022)
This study aimed to select the most suitable dam sites in the Wadi Numan watershed using GIS technology and hierarchical analysis process. Based on a series of steps and process, the study began with the construction of a geographic database of the study area, then criteria of spatial suitability of the dam construction site have been defined and selected based on expert opinion in similar study and literary references. These criteria consisted of a natural and human standard that have a direct impact on the selection of the appropriate dam’s site. On the basis of this, seven criteria have been identified and represented in the form of layer, which have been merged, after assigning a weight to each criterion according to its importance, with each other through the overlay mechanism and produce a map identifying suitable sites for dam location in the study area. The study found that the integration of GIS technology and hierarchical analysis process was effective in identifying the most suitable dam sites in the Wadi Numan watershed, where was obtained a map divided into five ranges in terms of the degree of suitability. Some of them are highly suitable, down to unsuitable ranges. The suitability map showed that (6%) of the total study area had high levels of suitability, (23%) suitability, (52%) medium suitability. while (31%) were poorly suitable and (15%) were unsuitable for the construction of dams. Based on this map, two dam sites of different sizes on Wadi Al Majarish (2.8 km2) and on Wadi Numan (3.5 km2) were identified as the two most suitable dam sites in the Wadi Numan watershed. The study recommends that the integration of GIS and hierarchical analysis techniques be used to achieve the objectives of geographical studies, and that a consistent ranking of standards be established according to their importance by experts and researchers and disseminated to all similar studies. The study recommends that the integration of GIS technology and hierarchical analysis process can be used to achieve objectives of geographical studies.